Research on the role and mechanism of the PI3K/Akt/mTOR signalling pathway in osteoporosis - Liu, Chuanlong; Zhang, Jianqiang; Ye, Ziyu; Luo, Ji; Peng, Bing; Wang, Zhexiang (Frontiers in Endocrinology, 2025)
Osteoporosis is a systemic metabolic bone disease characterised mainly by reduced bone mass, bone microstructure degradation, and loss of bone mechanical properties. As the world population ages, more than 200 million people worldwide suffer from the pain caused by osteoporosis every year, which severely affects their quality of life. Moreover, the prevalence of osteoporosis continues to increase. The pathogenesis of osteoporosis is highly complex and is closely related to apoptosis, autophagy, oxidative stress, the inflammatory response, and ferroptosis. The PI3K/Akt/mTOR signalling pathway is one of the most crucial intracellular signal transduction pathways. This pathway is not only involved in bone metabolism and bone remodelling but also closely related to the proliferation and differentiation of osteoblasts, osteoclasts, and bone marrow mesenchymal stem cells. Abnormal activation or inhibition of the PI3K/Akt/mTOR signalling pathway can disrupt the balance between osteoblast-mediated bone formation and osteoclast-mediated bone resorption, ultimately leading to the development of osteoporosis. This review summarises the molecular mechanisms by which the PI3K/Akt/mTOR signalling pathway mediates five pathological mechanisms, namely, apoptosis, autophagy, oxidative stress, the inflammatory response, and ferroptosis, in the regulation of osteoporosis, aiming to provide a theoretical basis for the development of novel and effective therapeutic drugs and intervention measures for osteoporosis prevention and treatment.